Examining the effect of regioisomerism on the physico-chemical properties of lysophosphatidylethanolamine-containing liposomes using fluoro probes. (November 2018) - Yamamoto, Yusuke; Furukawa, Takayuki; Takeda, Seiji; Kashida, Hiroyuki; Chiba, Hitoshi; Hui, Shu-Ping
Abstract: Lysophospholipids (LysoPLs) receive steadily increasing attention in the area of lipid chemistry and biology. However, the physico-chemical properties of individual LysoPL regioisomers have not yet been investigated. Herein, we report the synthesis of fluoro analogues of lysophosphatidylethanolamines (LPEs) and examine the physico-chemical properties of the LPE regioisomers using chemically synthesized fluoro probes.